Cytogenetic characterization of Rhomboplites aurorubens and Ocyurus chrysurus, two monotypic genera of Lutjaninae from Cubagua Island, Venezuela, with a review of the cytogenetics of Lutjanidae (Teleostei: Perciformes) - Nirchio, Mauro; Oliveira, Claudio [UNESP]; Ferreira, Daniela C. [UNESP]; Rondón, Rodolfo; Pérez, Julio E.; Hett, Anne Kathrin; Rossi, Anna Rita; Sola, Luciana (Sociedade Brasileira de Ictiologia, 2009)
Lutjanidae, comumente conhecidos como snappers, inclui 105 espécies, reunidas em quatro subfamílias. A despeito do grande número de espécies e de sua distribuição mundial, a família tem sido pouco estudada e as relações filogenéticas entre alguns de seus gêneros e espécies ainda é motivo de debates. Apenas um pequeno número de espécies foi citogeneticamente analisada. Esse estudo apresenta a primeira descrição do cariótipo de Rhomboplites aurorubens assim como dados relativos à distribuição de heterocromatina constitutiva e localização dos genes 18S rRNA e 5S rRNA. Espécimes de Ocyurus chrysurus da Venezuela foram também analisados quanto às mesmas características citogenéticas. Ambas as espécies têm cariótipos compostos de 48 cromossomos com um único braço, entretanto R. aurorubens tem um único par de cromossomos subtelocêntrico, o menor do complemento cromossômico, entre os outros cromossomos acrocêntricos. A heterocromatina C-positiva é limitada à região pericentromérica de todos os cromossomos. Ambas as species apresentam um único par com Regiões Organizadoras de Nucléolo, mas as RONs são localizadas em posições diferentes, em posição terminal no braço curto dos menores cromossomos de R. aurorubens e em posição paracentromérica no braço longo de um par de cromossomos grandes de O. chrysurus. em O. chrysurus, os genes 5S rDNA estão localizados em um par de cromossomos de tamanho médio, enquanto em R. aurorubens eles são sintenicamente localizados com os genes 18S rDNA no par de cromossomos número 24. Os dados citogenéticos obtidos, junto com os dados morfológicos e moleculares disponíveis para a família reforçam a proposta de sinonimizar o gênero Ocyurus com Lutjanus. Uma revisão da citogenética dos Lutjanidae é também apresentada

Lutjanidae, commonly known as snappers, includes 105 species, grouped in four subfamilies. In spite of the high number of species and of its worldwide distribution, the family has been little investigated and the phylogenetic relationships among some of its genera and species are still cause for debate. Only a small number of the species has been cytogenetically analysed. This study reports the first description of the karyotype of Rhomboplites aurorubens as well as data concerning the distribution of the constitutive heterochromatin and the location of the 18S rRNA and the 5S rRNA genes. Specimens of Ocyurus chrysurus from Venezuela were also investigated for the same cytogenetic features. Both species have a 48 uniarmed karyotype, but R. aurorubens has a single subtelocentric chromosome pair, the smallest of the chromosome complement, among the other acrocentric chromosomes. The C-positive heterochromatin is limited to the pericentromeric regions of all chromosomes. Both species show a single chromosome pair bearing the Nucleolus Organizer Regions, but NORs are differently located, in a terminal position on the short arms of the smallest chromosomes in R. aurorubens and in a paracentromeric position in a chromosome pair of large size in O. chrysurus. In O. chrysurus, the 5S rDNA gene cluster is located on a medium-sized chromosome pair, whereas in R. aurorubens it is syntenic with the 18S rDNA gene cluster on chromosome pair number 24. The obtained cytogenetic data, along with previous cytogenetic, morphological and molecular data for the family, reinforce the proposal to synonymize genus Ocyurus with Lutjanus. A review of Lutjanidae cytogenetics is also included.
Keywords: C-banding; FISH, Karyotype; NORs; Ribosomal genes